INFECTION AND INFLAMMATION: PROCESSES AND IMPLICATIONS (CIPEEX, 2025)
This abstract aims to promote the differentiation between infection and inflammation. The human body can defend itself through different mechanisms. When a pathogen invades the body seeking parasitism, benefiting at the expense of the infected host, infection occurs. Infection refers to the parasite-host relationship established between two or more living beings. In humans, infection can be caused by various etiological agents, such as viruses, bacteria, fungi, protozoa, and helminths. These agents are recognized by the immune system through innate and acquired immune responses.Innate immunity, present from birth, is rapid but nonspecific and acts as the first line of defense. Acquired immunity, on the other hand, is slower, develops after pathogen exposure, and is highly specific with immunological memory. It is mediated by B and T lymphocytes produced in the bone marrow and thymus.In addition to the immune response, infection can trigger inflammation, characterized by vascular, exudative, and cellular changes accompanied by pain, heat, redness, swelling, and loss of function. Inflammation can arise from external agents or endogenous tissue damage, aiming to eliminate harmful stimuli, promote healing, and restore tissue homeostasis.In summary, the differences between infection and inflammation lie in the stimulus origin and the response nature. Infection results from pathogen presence, while inflammation is a broader reaction to various aggressions. Both processes are essential for activating and modulating the immune response.
Keywords: immunity; infection; inflammation